Welfare-optimal status planning of minority languages: An economic approach - Bengt-Arne Wickström (Center for Economic Studies and ifo Institute (CESifo), 2011)
We analyze normatively determined distributions of language rights in multilingual settings. It is shown in a welfare-maximizing model where rights today influence the status of a language in the future, that the 'naive' ex ante cost-benefit analysis has to be augmented in various directions. This has its roots in the dynamic aspect of the rights and the resulting endogeneity of preferences as well as in the discrete character of rights. It is shown how efficiency and distribution considerations are affected by these considerations.
Keywords: D63; 330; minority rights; changeable preferences; dynamic preferences; welfare function; second-best analysis; overlapping generations; Sprachpolitik; Mehrsprachigkeit; Minderheitenpolitik; Soziale Wohlfahrtsfunktion; Overlapping Generations; Wohlfahrtseffekt; Theorie